THE ROLE OF L1 IN AN EYL CLASSROOM: PERCEPTIONS OF ELEMENTARY SCHOOL TEACHER AND STUDENTS - Hanny, Balqis Dhara (2015)
The importance of the use of L1 in the foreign language teaching has been rolled over decades. It has been a great deal of claims and counter-claims related to L1 use in L2 learning. However, children are rarely used as in-depth research, as opposed to teenager or adults (Cook, 1979 and Paradis, 2006). This study aims to investigate the role of Bahasa Indonesia (L1) in EYL classroom, as well as the perceptions of the teacher and the students towards it in english as a foreign language (EFL). To this end, twenty eight students and a teacher participated in classroom recordings and observations, semi-formal interview, and questionnaire. The results revealed that EYL teacher used Bahasa Indonesia in specific circumstances, such as encouraging the students, explaining vocabulary, giving instruction, and explaining grammatical rule. Moreover, the role played in the class, mostly are pedagogical and psychological role. Additionally, the teacher expressed that they never fall back on learners' L1 in the learning process. Also it was found that EYL students and the teacher believe that L1 was not the main point of the English lesson and played as a tool to help and clarify some context that have been learned. Keywords: Teacher and students' perceptions, English (L2), Bahasa Indonesia (L1), English for young learner (EYL), English as a foreign language (EFL).